Non-intrusive load monitoring and supplementary techniques for home energy management - Naghibi, Bahman; Deilami, Sara (IEEE, 2014)
The emerging smart grid technologies and rapid installations of smart meters is encouraging many consumers to implement home energy management systems (HEMSs) in order to decrease their electric utility bills and increase the efficiency of energy consumption. Intrusive load monitoring (ILM) and non-intrusive load monitoring (NILM) are two approaches in the literature for appliance load monitoring (ALM) that make it possible for HEMSs to optimize energy utilization. However, most researchers have addressed NILM as the more practical option. In this paper, three basic methods for NILM are presented and supplementary techniques for improving the accuracy of NILM are discussed and compared. In addition, future research directions and challenges are highlighted.